Platelet activation by ADP is increased in selected patients with anterior ischemic optic neuropathy or retinal vein occlusion - Claudia Kuhli-Hattenbach; Peter Hellstern; Thomas Kohnen; Lars-Olof Hattenbach (Platelets, 2017)
To investigate whether adenosine diphosphate (ADP)-induced platelet hyperaggregability is associated with nonarteritic anterior ischemic optic neuropathy (NAION) or retinal vein occlusion (RVO). We retrospectively reviewed thrombophilia screening data of patients with NAION or RVO without a history of arterial hypertension, diabetes mellitus, hyperlipidemia, obesity, and cigarette abuse. Patients with a positive family history for thromboembolism were not excluded. Platelet aggregation (area under the curve, AUC) after induction of 0.5, 1.0, and 2.0 µmol of ADP was estimated in 25 NAION and RVO patients and compared with 25 healthy controls. We observed significantly greater platelet aggregation post 0.5 (P = 0.002) and 1.0 (P = 0.008) µmol of ADP among NAION and RVO patients compared with healthy controls. Platelet hyperaggregability was significantly more prevalent in patients than in controls (56% vs. 8%; P = 0.0006). Our results suggest that in NAION and RVO patients without a history of arterial hypertension, diabetes mellitus, hyperlipidemia, obesity, and cigarette abuse, platelets are significantly hyperreactive after induction of very low concentrations of ADP when compared with healthy individuals. This hyperreactivity is particularly evident in patients with a family history of thromboembolism.